Analysis, Assessment for Potential Development of the Central Regional Clusters to Prepare Master Planning of Socio-economic Development in the Context of Economic Integration - Dong, Hoang Sy; Lan, Nguyen Thi Thu; Vinh, Nguyen Quang (World Bank, Washington, DC, 2013)
This report provides an analysis of the land and water resources, as required by the World Bank, and focuses particularly on sea ports and potential tourism. The analysis identifies shortcomings, challenges, opportunities and advantages in competitive operations, that would make the best use of internal resources. The report also looks at Issues in industrialization and modernization. At present, the Prime Minister assigned the Ministry of Planning and Investment (MPI) to prepare the regional development planning until 2020 for 6 main regions. Therefore, the report revisits the socio-economic development plan for the north-central region and south-central coast until 2010, as an necessary objective to ensure quality improvement and feasiblity of the plans.